Who misses the target when thinking? Soccer expertise influences shooting-accuracies under cognitive load - Schaefer, S.; Leisge, K. (International Journal of Sport and Exercise Psychology, 2025)
Soccer is a highly dynamic game involving constant cognitive and motor challenges. Players have to make clever strategic decisions, while also performing the required motor response successfully. The current study uses a cognitive-motor dual-task paradigm to reveal expertise differences in the ability to keep up shooting accuracies under increasing levels of cognitive load. 120 soccer players from 6 teams that differed in expertise (Local League to Bundesliga) were asked to perform a spatial working memory task, N-back, while shooting at one out of 10 segments of a soccer goal. Task-difficulties ranged from N-back0 (single-task shooting) to N-back3 (shooting at the target that was illuminated three positions earlier). For cognitive single-tasks, participants pointed at the target location instead of shooting. Participants showed cognitive performance decrements in N-back under dual-task conditions. Shooting accuracies for the correct N-back location also showed strong decrements, which were even larger in players from the lower ability groups. However, for the shooting accuracy to the target location that a participant aimed at (independent of whether this was a correct target concerning N-back), higher-league players showed no performance decrement from N-back0 to N-back3. Shooting accuracies of players of the lowest league suffered from dual-tasking. It is concluded that most soccer players perform overlearned motor skills on the soccer field successfully, even under high cognitive load. However, the accuracy of strategic decisions may suffer in challenging situations. Soccer-specific dual-task situations can identify superior players, over and above standardised cognitive task.